The Role of Morphology and Sentence Context in Word Processing for Adults With Low Literacy. - Tremblay, Kathryn A.; McBane, Katja; Binder, Katherine S. (Journal of Learning Disabilities, 2026)
Both vocabulary skill and morphological complexity, or whether words can be broken down into root words and affixes, have a significant impact on word processing for adults with low literacy. We investigated the influence of word-level variables of morphological complexity and root word frequency, and the sentence-level variable of context strength, on word processing in adults with low literacy, who differed on levels of vocabulary depth skills, which was a participant-level variable. Our findings demonstrate that morphological complexity, root word frequency, and context strength are all related to how adult learners process words while reading, but their effects are dependent on participants' vocabulary depth. Participants with higher levels of vocabulary depth were able to more quickly process morphologically complex words and make better use of supportive sentence context as compared to individuals with lower levels of vocabulary depth. These findings suggest that both morphological complexity and vocabulary depth are important for word processing and reading comprehension in adults with low literacy.